1979
DOI: 10.1002/jmv.1890030405
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B core antibody in volunteer blood donors: Comparison of radioimmunoassay and indirect immunofluorescence

Abstract: The results of a pilot study on the prevalence of anti-HBc in HBsAg negative volunteer blood donors are presented. Two techniques for anti-HBc determination were compared--radioimmunoassay (RIA) and indirect immunofluorescence (IF). In a panel of 56 sera with known HBV markers, RIA was found to be significantly more sensitive than IF, and both techniques were specific. Out of 2,000 HBsAg negative blood donor sera tested by RIA, 46 (2.3%) were found positive for anti-HBc. In 24/24 sera, the specificity of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1980
1980
1988
1988

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The ratios of anti-HBc positive in blood donors are reported to be 2-3% in the USA (Irwin et al 1977;Nath et al 1983) and the Netherland (Katchaki et al 1979), and 11% in Italy (Ascione et al 1981). As shown in Fig.…”
Section: Discussionmentioning
confidence: 82%
“…The ratios of anti-HBc positive in blood donors are reported to be 2-3% in the USA (Irwin et al 1977;Nath et al 1983) and the Netherland (Katchaki et al 1979), and 11% in Italy (Ascione et al 1981). As shown in Fig.…”
Section: Discussionmentioning
confidence: 82%
“…The overall prevalence of anti-HBc among volunteer blood donors using ra dioimmunoassay or complement fixation tests has been reported as 2.3% in The Neth erlands [10], 15.3% in Greece [15], 33.3% in Italy [2], and 2.7% in the United States [16], The prevalence of anti-HBc among blood donors in 13 countries in the western hemi sphere was 21%, and 5.3% of all blood do nors had anti-HBc as the sole marker of HBV infection [12], A higher prevalence of anti-HBc has been reported in volunteer blood donors who present with a history of hepatitis or transfusion [17] and among some US military populations [8], The observed prevalence of HBsAg is significantly affected by the donor selection practices and depends upon the proportion of blood collected at a particular type of site, e.g., schools and col leges, plants and factories, on military bases, etc., which in turn reflects the different so cioeconomic status of the donor populations [3]. It is not clear from the data available to us if the lower prevalence of anti-HBc in Boston reported here was due to the differ ences in the type of blood collection sites.…”
Section: Discussionmentioning
confidence: 99%
“…In such subjects, antibodies of the IgM class are often absent or present in very low titers (9). Determination of anti-HBc has been extensively employed in epidemiological studies (13) and is demonstrated to be a more sensitive indicator than antibody to hepatitis B surface antigen (anti-HBs) of past HBV infection (5).…”
mentioning
confidence: 99%